Optimalisasi Program Literasi dan Numerasi untuk Membangun Generasi Cerdas melalui Pendampingan Terstruktur di SDN Grujugan Larangan - Moh.Hamzah; Abubakar Basyarahil; Fajar surahman; Abdurahman Abdurahman; Isnain Bustaram; Zainurrafiqi Zainurrafiqi; Nurul Hidayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Literacy and numeracy programs play a crucial role in improving education quality, especially at the elementary school level. This study aims to optimize literacy and numeracy programs through a structured mentoring approach at SDN Grujugan Larangan, Larangan Luar Village, Larangan Subdistrict, Pamekasan Regency. The research method used is action research with qualitative and quantitative approaches. The qualitative approach is used to understand teachers' and students' perceptions of the mentoring program, while the quantitative approach is applied to measure the improvement in students' literacy and numeracy skills after participating in the program. The results indicate that structured mentoring significantly enhances students' literacy and numeracy skills, as evidenced by the increased average scores in reading, writing, and arithmetic. Furthermore, active teacher involvement in the mentoring process contributes to the program's success. Thus, implementing a structured mentoring program can be an effective model to improve the quality of primary education in rural areas.